The Reconstruction of Sufism Learning for Madrasah Teachers through the Hermeneutical Approach of Islamic Education - Jasminto (Journal Of Islamic Education And Pesantren, 2026)
Sufism instruction in madrasahs has long tended to be reduced to ritualistic practices and individual moral cultivation, thereby limiting its function as a transformative pedagogical framework for teachers. This article aims to reconstruct Sufism learning for madrasah teachers through the lens of Islamic educational hermeneutics, positioning Sufism as a contextual and reflective praxis of meaning-making. Employing a qualitative–conceptual approach, this study is based on a critical literature review of classical and contemporary Sufi texts, alongside key works in Islamic educational hermeneutics. The analysis proceeds through historical, dialogical, and applicative stages to bridge the meanings of Sufi texts with the pedagogical realities faced by madrasah teachers. The findings demonstrate that a hermeneutical approach enables Sufism to be reinterpreted as a foundational learning framework that integratively cultivates ethical, spiritual, and pedagogical consciousness. This reconstruction situates teachers not merely as transmitters of religious knowledge, but as reflective subjects capable of interpreting, internalizing, and transforming Sufi values within educational practice. The article contributes to the advancement of Islamic education paradigms by offering a model of Sufism learning that is contextual, dialogical, and responsive to the challenges of contemporary madrasah education.